2D-on-2D core–shell Co3(PO4)2 stacked micropetals@Co2Mo3O8 nanosheets and binder-free 2D CNT–Ti3C2TX–MXene electrodes for high-energy solid-state flexible supercapacitors. Issue 46 (16th November 2021) - Patil, Amar M.; Chodankar, Nilesh R.; Jung, Euigeol; Roy, Sanjib; Dubal, Deepak P.; Guan, Guoqing; Han, Young-Kyu; Jun, Seong Chan
Abstract : (a) Assembly of the FHSC device; (b) the excellent electrochemical performance of FHSC device. Abstract : The structural instability and sluggish kinetics of conventional positive electrodes with the lower capacitance of carbon-based negative electrodes result in an inferior performance for state-of-art supercapacitors (SCs). A general yet sustainable approach is proposed here to overcome this hitch by assembling hybrid SC cells utilising porous and stable 2D-on-2D core–shell and carbon/pseudocapacitive composite electrodes. Porous Co3 (PO4 )2 transparent stacked micropetals (TSMs) were synthesised and decorated with Co2 Mo3 O8 nanosheets (NSs) (Co3 (PO4 )2 @Co2 Mo3 O8 ) forming a 2D-on-2D core–shell positive electrode, which was combined with a 2D carbon nanotube/MXene (CNT–Ti3 C2 T X ) composite negative electrode. The core–shell electrode achieved a specific capacity of 184.7 mA h g −1 (738 mF cm −2 ) and cycling stability of 95.6% over 15 000 charge/discharge cycles. The CNT–Ti3 C2 T X electrode exhibited a remarkable areal capacitance of 187.5 mF cm −2 and cycling stability of 93.1%. Consequently, the assembled unique hybrid solid-state SCs delivered an exceptional volumetric capacitance of 7.9 F cm −3 and a specific energy of 74.06 W h kg −1 (2.47 mW h cm −3 ) at a specific power and cycling stability of 1.13 kW kg −1 and 93.2%, respectively. Overall, the techniques and electrode materials presented in this study can serve as a reference to produce a range of electrode materials for next-generation energy storage devices.